2001
DOI: 10.1051/lait:2001139
|View full text |Cite
|
Sign up to set email alerts
|

Effets de différents traitements de correction sur les aptitudes à la coagulation des laits de chèvre, de brebis et de vache chauffés

Abstract: Effect of calcium addition, acidification, ultrafiltration and storage on renneting properties of heated goat's, ewe's and cow's milks. The effects of calcium addition, acidification, protein concentration by ultrafiltration and 24 h storage at 25 o C have been studied in cow's milk, goat's milk and ewe's milk heated at 80 o C during 1 and 10 min. Among the three types of milk, cow's milk is the one whose renneting properties were the most strongly impaired by heating. Technological treatments which were appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…This influence has been the subject of various studies that are not always in agreement. For example, Remeuf and Raynal (2001) showed that the adjunction of calcium to cow's and ewe's milks improves the drainage ability. However according to Walstra and Jenness (1984), it has been established the negative impact of calcium on DC.…”
Section: Relationships Between Drainage Capacity and Physicochemical mentioning
confidence: 99%
“…This influence has been the subject of various studies that are not always in agreement. For example, Remeuf and Raynal (2001) showed that the adjunction of calcium to cow's and ewe's milks improves the drainage ability. However according to Walstra and Jenness (1984), it has been established the negative impact of calcium on DC.…”
Section: Relationships Between Drainage Capacity and Physicochemical mentioning
confidence: 99%